Exploring career decisions and employability skills among engineering students in vocational colleges - Bakry, Nurul Shazwani; Mohd Puad, Mohd Hazwan; Asimiran, Soaib; Abd. Kadir, Suhaida; Mat Rashid @ Mat Idris, Abdullah (Human Resource Management Academic Research Society, 2020)
Malaysia is committed to achieving sustainable growth along with fair and equitable distribution across income groups, ethnicities, regions, and supply chains. The commitment aims to enhance the nation’s prosperity and be prepared with a sufficient skilled and semi-skilled workforce. However, there is a lack of proficiency and sensitivity of the technical and vocational graduates for the various career-enhancing programs organized by the government. The graduates do not have clear action plans and strategies to meet the needs of the industrial market. In addition, there is a concern from the industries about the graduates’ job skills to succeed in their careers. Therefore, this study aimed to explore career decisions and the level of employability skills based on gender, academic achievement, and career exposure among engineering students in vocational colleges in Selangor, Malaysia. The researcher used a survey design and quantitative approach for this research. Respondents for this study are the first and second year of engineering students in Selangor vocational colleges. The findings show that the level of career decision and employability skills are at a moderate high level for most demographic groups. This study also serves as a reference to stakeholders to identify students’ career decisions and employability skills in vocational colleges. Administrators and educators are recommended to play an active role in integrating career information and guidance in the learning process efficiently in order to improve students’ career decisions and employability skills.